The Influence of Mothers' Knowledge Towards Their Perceived Behavioral Control - Putri, Tiara Amelia; Gracia, Amanda Bunga; Destiwati, Rita (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2024)
This research explores the environmental impact of baby formula production and its influence on breastfeeding rates, particularly in Asia. It highlights the role of the Breastfeeding Mother Community on Facebook in raising awareness among mothers, despite a lack of content on the environmental drawbacks of formula milk. The study aims to assess community members’ knowledge of these impacts and its effect on their behavior. Using the TPB theory, it investigates the link between environmental knowledge and perceived behavioral control. The research uses a quantitative approach, using questionnaires, with a sample of 400 respondents from the community. This research employs various data analysis techniques, including descriptive analysis, normality test, simple linear regression analysis, hypothesis testing, and the coefficient of determination test. The findings reveal that the knowledge of the Breastfeeding Mother Community members on Facebook about the environmental impact of formula milk production influences their perceived behavioral control by 28.2%. The remaining percentage is influenced by variables not covered in this research. However, the results indicate no significant influence, as evidenced by the calculated T value being greater than the T table (-4.742 1.965), leading to the rejection of H1 and acceptance of H0.